2002
DOI: 10.1309/evxt-851x-whlc-rlx9
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Follow-up of People With Celiac Disease on a Gluten-Free Diet

Abstract: To assess histologic recovery in response to gluten withdrawal in celiac disease, 158 patients seen in our hospital during a 15-year period underwent follow-up small intestine biopsies (SIBs) within 2 years after starting a gluten-free diet; further SIBs were done if villous atrophy was present. A modified Marsh classification was used (IIIA, partial villous atrophy; IIIB, subtotal villous atrophy; IIIC, total villous atrophy). Of patients with Marsh IIIA, IIIB, or IIIC lesions, histologic remission was seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
224
2
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(248 citation statements)
references
References 12 publications
15
224
2
7
Order By: Relevance
“…[18][19][20] Our data suggest that the reported MIF levels would not be a consequence of the inflammatory process, but they would be directly involved in the etiology of the disease. Functional studies on the role of the polymorphisms tested have been performed in the past with controversial findings reported in different cell types; [21][22][23] however, the (CAAT) 5 allele was associated with reduced basal and serum/forskolin-stimulated transcriptional activity in vitro [21][22][23] and the (CAAT) 7 and À173C alleles emerged as probable upregulators of transcriptional activity.…”
Section: à7mentioning
confidence: 70%
“…[18][19][20] Our data suggest that the reported MIF levels would not be a consequence of the inflammatory process, but they would be directly involved in the etiology of the disease. Functional studies on the role of the polymorphisms tested have been performed in the past with controversial findings reported in different cell types; [21][22][23] however, the (CAAT) 5 allele was associated with reduced basal and serum/forskolin-stimulated transcriptional activity in vitro [21][22][23] and the (CAAT) 7 and À173C alleles emerged as probable upregulators of transcriptional activity.…”
Section: à7mentioning
confidence: 70%
“…They must recommend a strict adherence to a GFD for patients with CD, and be aware of the appearance of autoimmune diseases (67) . In addition, professionals should re-study the patients with different symptoms or clinical deterioration with the objective of an early diagnosis of malignancies (72) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that histological recovery after starting a GFD takes time (more than 2 years in 35% of the patients) and that 10% of the patients present incomplete or non recovery. The risk of this group of patients developing a malignant neoplasma is undefined thus far, and should be further investigated (72) .…”
Section: Lymphomasmentioning
confidence: 99%
“…Recent studies have shown that more than 50% of adults do not recover from villous atrophy, even after two years on a proper diet [32] . In the case of children, even though information is limited, there is duodenal mucosa recovery in the vast majority (95%) during the first two years after the diagnosis [33] . The main cause of this lack of mucosal recovery in adults could be the continuous and inadvertent ingestion of small amounts of gluten.…”
Section: Evolution and Prognosismentioning
confidence: 99%